INOVASI PUDDING JAGUNG SEHAT SEBAGAI UPAYA PENCEGAHAN STUNTING PADA IBU HAMIL DAN ANAK-ANAK DI DESA MEKAR SARI - Pratama, Reza Hardian; Farros, M.Dzaki; Anjelika, Desti; Koiriyah, Koiriyah; Septiani, Septiani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Community Service Program students focused on stunting prevention through balanced nutrition counseling, parenting practices, and demonstrations on making corn pudding, a nutritious food. Stunting caused by chronic malnutrition can hinder physical growth and cognitive development, and increase the risk of chronic diseases in the future. Therefore, the involvement of pregnant women, parents, community service post (Posyandu) cadres, and health workers is crucial in this program. Corn was chosen as the main ingredient because it is readily available, affordable, and rich in nutrients, making it a practical, healthy snack alternative for the community. The results of the activities showed an increase in community knowledge about nutrition and practical skills in processing local foods, which is expected to reduce stunting rates and support the creation of a healthy, intelligent, and productive generation in Muara Dua Village.